Effects of Acute Intracerebroventricular Microinfusions of Bupropion on Background Spike Activity of Locus Coeruleus Neurons in Rats - Pakdel, F.G.; Amirabadi, S.; Naderi, S.; Osalou, M.A.; Cankurt, U.; Jahanbani, M.; Shahabi, P. (Нейрофизиология, 2014)
Considering that noradrenergic (NAE) neurons of the locus coeruleus (LC) play significant
roles in the formation of biological rhythms, pain, addictions, and mood disorders, we tested
the effects of acute intracerebroventricular microinfusions of bupropion, an inhibitor of NA
reuptake used in clinics as an antidepressant, on background spike activity on LC neurons in
chloral-hydrate anesthetized rats. Ten microliters of the solutions containing 0.001, 0.01, 0.1,
1.0, or 10.0 µmol bupropion were infused during 3 min; spike activity of single LC neurons
identified according to the known characteristics was recorded extracellularly by glass microelectrodes. Microinfusions of 0.01 to 10.0 µmol bupropion suppressed background spiking of the above neurons in a dose-dependent manner. The normalized mean intensities and
durations of inhibition were 17.3, 19.4, 26.3, and 41.1% and 1.4, 7.1, 12.4, and 18.3 min,
respectively. The smallest dose (0.001 µmol) was ineffective. It is assumed that bupropion
increases the NA level in proximity to NAE LC neurons. The actions of bupropion on other
cerebral neuromodulatory systems need further examination. Inhibition of LC neuronal activity by bupropion can help to explain some acute, chronic, and side effects of this agent used
in clinics for correction of mood disorders. Враховуючи, що норадренергічні (НАЕ) нейрони блакитної плями (locus coeruleus – LC) відіграють істотну
роль у формуванні біологічних ритмів, болю, фармакологічних залежностей та розладів настрою, ми тестували
впливи гострих інтрацеребровентрикулярних мікроінфузій антидепресанта бупропіону на фонову активність нейронів LC у щурів. Уводили 10 мкл (тривалість інфузій
3 хв) розчинів, що вміщували різні дози (0.001, 0.01, 0.1,
1.0 або 10.0 мкмоль) бупропіону – інгібітора зворотного захоплення норадреналіну, що використовується в клініці як антидепресант. Імпульсну активність поодиноких
нейронів LC відводили позаклітинно скляними мікроелектродами. Мікроінфузії 0.01–10.0 мкмоль бупропіону дозозалежно пригнічували фонову імпульсацію цих нейронів. Середня нормована інтенсивність та тривалість гальмування
складали в даних випадках 17.3, 19.4, 26.3 і 41.1 % та 1.4,
7.1, 12.4 і 18.3 хв відповідно. Найменша доза бупропіону
(0.001 мкмоль) була неефективною. Вважається, що бупропіон зумовлює підвищення рівнів цього катехоламіну в зоні
розташування НАЕ-нейронів LC. Взаємодія бупропіону з
іншими центральними нейромодуляторними системами потребує подальшого вивчення. Факт гальмування нейронної
імпульсної активності в LC під впливом бупропіону може
сприяти інтерпретації особливостей гострих та хронічних
впливів цього агента та його побічних ефектів при застосуванні в клініці для корекції розладів настрою.